2001
DOI: 10.1509/jmkr.38.1.3.18834
|View full text |Cite
|
Sign up to set email alerts
|

Truth or Consequences: An Analysis of Vaporware and New Product Announcements

Abstract: The software industry practice of announcing new products well in advance of actual market availability has led to allegations that firms are intentionally engaging in vaporware. The possible predatory and anticompetitive implications of this behavior recently surfaced in the antitrust case United States v. Microsoft Corporation. Taking the perspective that a new product announcement is a strategic signal among firms, the authors consider the possibility that intentional vaporware is a way to dissuade competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
132
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 34 publications
0
132
0
3
Order By: Relevance
“…For instance, Bayus, et al (2001) present a model in which product preannouncement is used as a strategic signal for rival firms. In the paper, intentional vaporware is used as a way to dissuade competitors from developing their own competing products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Bayus, et al (2001) present a model in which product preannouncement is used as a strategic signal for rival firms. In the paper, intentional vaporware is used as a way to dissuade competitors from developing their own competing products.…”
Section: Introductionmentioning
confidence: 99%
“…Our proposal, in contrast, intends to analyze a communication channel between the firm and consumers. Thus, the purpose of product preannouncement in Bayus, et al (2001) is entry deterrence, whereas the purpose of our model is to persuade consumers to wait until the arrival of its new product. 3 Also, Bayus, et al adopt an ad hoc assumption that making a false announcement is costly, without any micro-foundation for penalty costs associated with false announcements.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wu, Balasubramanian, and Mahajan [40] found that 70 % of key informants in the computer hardware, software, and telecommunications industries had encountered some delay when introducing a preannounced product and launched it several weeks after the announced date. Forty-seven percent of a sample of software products studied by Bayus, Jain, and Rao [21] has been launched with a delay over 3 months compared to their announced release date. Whether the company intends to announce a vaporware or originally intends to launch the product at the announced date but has experienced some delay in the new product development, the frequent preannouncement delays induce consumers to question the chances that the launch will actually occur at the launch date.…”
Section: Credibility Factormentioning
confidence: 99%
“…Firms preannouncing their new products choose very different timing strategies, from a few weeks to several years before market introduction [21,45,46]. As Lilly and Walters [47] note, even though the announcement timing can significantly affect a new product's success, the marketing and economics literature provides few insights and guidelines on this component of a launching strategy.…”
Section: When Should a Firm Preannounce The Launch Of Its New Product?mentioning
confidence: 99%
See 1 more Smart Citation